Peptides derived from Plasmodium falciparum leucine-rich repeat 1 bind to serine/threonine phosphatase type 1 and inhibit parasite growth in vitro - Pierrot C; Zhang X; Zanghi G; Fréville A; Rebollo A; Khalife J (Dove Medical Press, 2018)
Christine Pierrot,1 Xiguang Zhang,2 Gigliola Zhangi,2 Aline Fréville,1 Angelita Rebollo,2 Jamal Khalife1 1Center for Infection and Immunity of Lille, U1019 – UMR 8204, Institut Pasteur de Lille, Université de Lille, Lille Cedex, 2CIMI Paris, UPMC/Inserm U1135, Paris, France The biogenesis of protein phosphatase 1 (PP1) holoenzyme in eukaryotes requires diverse regulatory subunit proteins (RSPs) that bind to the highly conserved PP1 catalytic subunit (PP1c) and direct its spatiotemporal activity as well as its specificity. Several studies demonstrated that most RSPs share a canonical common binding motif, the RVXF motif, which is present in ~85% of RSPs and is considered as the main contributor for the interaction to PP1c.1 In Plasmodium falciparum (Pf), our earlier studies revealed that leucine-rich repeat 1 (LRR1), one of the major RSPs of PfPP1 and an ortholog of human and yeast Sds22, lacks the RVXF motif. The amino acids sequence of PfLRR1 exhibits nine leucine-rich repeats (LRRs) and a hydrophobic region at the C-terminal end, known as the LRR cap motif.2 In this work, we identified the PP1-binding peptides of PfLRR1 and examined their capacity to affect Pf growth.